Collaborative work with Akademi Farmasi Indonesia Yogyakarta (AFIYO) / Nurul Alyaa Ibrahim and Associate Prof. Dr. Mahmathi Karuppannan - Ibrahim, Nurul Alyaa; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
Following the signing of a memorandum of understanding (MOU) with Indonesian partners, the Faculty of Pharmacy, UiTM Bertam Campus (FoP Bertam) strives to continue strengthening the collaboration between the two countries through collaborative knowledge transfer projects. On 5th of August 2023, FoP Bertam and Akademi Farmasi Indonesia Yogyakarta (AFIYO) co-organized a webinar with the theme “Optimizing Natural Ingredients as a Pharmapreneur Idea for Advanced of Indonesia''.